Association between dietary diversity, sedentary time outside of work and depressive symptoms among knowledge workers: a multi-center cross-sectional study - Lijun Li; Pingting Yang; Yinglong Duan; Jianfei Xie; Min Liu; Yi Zhou; Xiaofei Luo; Chun Zhang; Ying Li; Jiangang Wang; Zhiheng Chen; Xiaohong Zhang; et al. (BMC, 2024)
Abstract Background Low-diversity diets and sedentary status are risk factors for depressive symptoms, while knowledge workers were ignored before. The purpose of this current study was to examine the relationship between dietary diversity, sedentary time spent outside of work, and depressive symptoms among knowledge workers. Study design and methods This was a multicenter and cross‐sectional design that included 118,723 knowledge workers. Participants self-reported online between January 2018 and December 2020. Demographic information, the Dietary Diversity Scale, the Patient Health Questionnaire-9, dietary habits (which included eating three meals on time, midnight snacking, overeating, social engagement, coffee consumption, sugary drink consumption, smoking and alcohol use), sedentary time spent outside of work and physical activity were investigated. Results The relationships between demographic information, dietary habits and dietary diversity, and depressive symptoms were estimated. Compared with the first and second levels of dietary diversity, the third level of dietary diversity (OR: 0.91; 95% CI: 0.84-0.98) reduced the risk of depressive symptoms. Knowledge workers with different degrees of sedentary status (2-4 h (OR: 1.11; 95% CI: 1.07-1.14), 4-6 h (OR: 1.21; 95% CI: 1.17-1.26), and > 6 h (OR: 1.49; 95% CI: 1.43-1.56), presented a progressively higher risk of depressive symptoms. Conclusion High amounts of sedentary time spent after work and low levels of dietary diversity are risk factors for depressive symptoms. In addition, an irregular diet and overeating are also major risk factors for knowledge workers.